Nutrient combinations exhibit universal antianxiety, antioxidant, neuro-protecting, and memory-improving activities - Zhao, Bangcheng; Jia, Xiuzhen; Feng, Haotian; Tang, Cheng; Huang, Yixin; Zhao, Zifu; Hao, Jingyu; Li, Haoqiu; Du, Jinrui; Liu, Yan; Bao, Xingyu; Zhong, Zhihui; et al. (Frontiers in Nutrition, 2023)
Anxiety disorders are the most common mental disorders and, without proper treatment, may lead to severe conditions: e.g., somatic disorders or permanent damage to central nervous system. Although there are drugs in clinical trials, this study focuses on exploring the efficacy of nutrients in treating these diseases. We built different zebrafish models and screened several nutrient combinations for their antianxiety, antioxidant, neuro-protecting and memory-improving activities. Our results showed that the combinations of nutrients (e.g., Walnut Peptides + Theanine at 14.2 + 33.3 μg/mL) have similar or better activities than the positive control drugs. In addition, we discovered that the effects of the nutrients in the above four aspects were universal and highly related. This study is noteworthy as it suggested that nutrients could be healthier and greener drug alternatives and provide similar or better universal treatments for anxiety and related conditions.